Novel Hyaluronate Lyase Involved in Pathogenicity of Streptococcus dysgalactiae subsp. equisimilis - Nguyen, Van An; Ogura, Kohei; Matsue, Miki; Takemoto, Norihiko; Mukai, Kanae; Nakajima, Yukari; Hoang, Thuy Linh; Iwata, Yasunori; Sakai, Norihiko; Wada, Takashi; Hashimoto, Wataru; Okamoto, Shigefumi; et al. (Frontiers in Microbiology, 2020)
Streptococcus dysgalactiae subsp. equisimilis (SDSE) causes cellulitis, bacteremia, and invasive diseases such as streptococcal toxic shock syndrome. Although SDSE infection is more prevalent among the elderly individuals and those with diabetes mellitus than infections with S. pyogenes (Group A streptococci; GAS) and S. agalactiae (Group B streptococci; GBS), the mechanisms underlying the pathogenicity of SDSE remain unknown. SDSE possesses a gene hylD encoding a hyaluronate lyase (HylD), whose homologues (HylB) is involve in pathogenicity of GBS, while role of HylD had not been characterized. In this study, we focused on the enzyme HylD produced by SDSE; HylD cleaves hyaluronate (HA) and generates unsaturated disaccharides via a β-elimination reaction. Hyaluronate-agar plate assays revealed that SDSE promoted dramatic HA degradation. SDSE expresses both HylD and an unsaturated glucuronyl hydrolase (UGL) that catalyzes the degradation of HA-derived oligosaccharides; as such, SDSE was more effective at HA degradation than other β-hemolytic streptococci, including GAS and GBS. Although HylD shows some homology to HylB, a similar enzyme produced by GBS, HylD exhibited significantly higher enzymatic activity than HylB at pH 6.0, conditions that are detected in the skin of both elderly individuals and those with diabetes mellitus. We also detected upregulation of transcripts from hylD and ugl genes from SDSE wild type collected from the mouse peritoneal cavity; upregulated expression of ugl was not observed in ΔhylD SDSE mutants; these results suggested that disaccharides produced by the actions of HylD are capable of triggering downstream pathways that catalyze their destruction. Furthermore, we determined that infection with SDSEΔhylD was significantly less lethal than infection with the parent strain. When mouse skin wounds were infected for 2 days, intensive infiltration of neutrophils was observed around the wound areas infected with SDSE wild type but not SDSEΔhylD. Our investigation suggested that HylD and UGL play important roles in nutrient acquisition from hosts, followed by the bacterial pathogenicity damaging host tissues.